The Effect of Burnout towards Organizational Citizenship Behaviour, Mediated by Job Satsifaction in XYZ Company, Surabaya - Renaldo Prasetyo (iBuss Management, 2015)
The purpose of this research was to investigate the effect of Burnout towards Organizational Citizenship Behavior, mediated by Job Satisfaction in XYZ Company, Surabaya. The data gathered using simple random sampling method and the questionnaires obtained from 80 respondents whom work as permanent employee in XYZ Company. Among 80 Questionnaires obtained, only 70 Questionnaires are valid and able to be analyzed. Then the data being analyzed by Multiple Linear Regression and Tested for mediation. The result shown that Burnout simultaneously and individually having significant impact toward OCB. However in testing for mediation, Job Satisfaction is found out not to be the mediating factor between the relationships of Burnout towards OCB. Keywords: Burnout, Organizational Citizenship Behavior, Job Satisfaction